2006
DOI: 10.1111/j.1574-6968.2006.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the major staphylococcal autolysin Atl

Abstract: The major autolysin of Staphylococcus aureus (AtlA) and of Staphylococcus epidermidis (AtlE) are well-studied enzymes. Here we created an atlA deletion mutant in S. aureus that formed large cell clusters and was biofilm-negative. In electron micrographs, the mutant cells were distinguished by rough outer cell surface. The mutant could be complemented using the atlE gene from S. epidermidis. To study the role of the repetitive sequences of atlE, we expressed in Escherichia coli the amidase domain encoded by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
282
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(290 citation statements)
references
References 34 publications
8
282
0
Order By: Relevance
“…In Staphylococcus epidermidis and S. aureus, disruption of the atl gene, encoding the primary murein hydrolase of these bacteria, causes a dramatic decrease in their abilities to form biofilm (65,66). Inactivation of a gene encoding an Atl homolog in S. mutans also reduced its biofilm-forming ability (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…In Staphylococcus epidermidis and S. aureus, disruption of the atl gene, encoding the primary murein hydrolase of these bacteria, causes a dramatic decrease in their abilities to form biofilm (65,66). Inactivation of a gene encoding an Atl homolog in S. mutans also reduced its biofilm-forming ability (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…The three-Atlrepeat domain, R 1-3 (17,18), was expressed with a N-terminal His 6 tag in Escherichia coli M15 using the isopropyl-␤-D-thiogalactopyranoside (IPTG)-inducible plasmid pEQ30Atl R [1][2][3] (19,20). Cells were cultivated in 2ϫ yeast extract-tryptone broth (YT) to an OD of 0.5 at 37°C and then induced with 0.5 mM IPTG for 4 h at 20°C.…”
Section: Methodsmentioning
confidence: 99%
“…It was also shown that mutation of tarO results in delocalization of amidase (21). Atl possesses three repeat sequences, each about 150 amino acids long (R 1-3 ), which bind to peptidoglycan (19,35). We examined the localization of Atl using a fluorescently labeled R 1-3 repeat domain (Cy3-R 1-3 ) (21).…”
Section: Teixobactin-induced Lysis Is Dependent On the Atl Autolysinmentioning
confidence: 99%
“…Production of the icaADBC operon-encoded polysaccharide intercellular adhesin (PIA) or polymeric N-acetylglucosamine (PNAG) remains the best-understood mechanism of biofilm accumulation in staphylococci (Mack et al, 1996;Maira-Litrán et al, 2002;O'Gara, 2007). The major cell wall-anchored autolysins AtlA and AtlE, in S. aureus and S. epidermidis, respectively, have been implicated in the primary attachment stage of biofilm production (Biswas et al, 2006;Heilmann et al, 1997). Atl contains amidase (Ami) and glucosaminidase (GL) domains separated by three direct repeats, R 1 , R 2 and R 3 .…”
Section: Introductionmentioning
confidence: 99%